Talking methods, talking about methods: Invoking the transformative potential of social methods through animals, objects and how‐to instructions. Issue 1 (23rd March 2022) - Pottinger, Laura; Barron, Amy; Hall, Sarah Marie; Ehgartner, Ulrike; Browne, Alison L.
Abstract: This paper focuses on "talking" methods, noting their wide application across the social sciences, and identifies potential spaces for innovation in this field. Drawing on interview material from the Methods for Change project, we argue that researching methods requires creative approaches to talk. With research methods as our focus, we draw on data collected from online interviews with 36 academics, which aimed to explore the transformative potential of social science research methods. We make three contributions. First, we consider challenges and potentials for talking about methods and communicating the transformative potential of social science methods to diverse audiences. Second, we elaborate on the detail of doing talking methods, identifying potential spaces for innovation. Third, we suggest there is value in supplementing interviews with creative techniques when talking with and about method. We highlight three such techniques used in our project as a means of eliciting conversation about the transformative potential of methods: how‐to instructions; object interviewing; and methods as animals. The conceptual underpinnings, practical applications and obstacles encountered with each technique are discussed, including our own reflections on creative interviewing in a context where face‐to‐face research was restricted. In doing so, we respond to and advance recent debates about the need to talk more about the doing of talking methods. We argue that academics need to articulate why methods matter in creating change to global challenges, and that creative techniques can play a pivotal role. Abstract : This paper focuses on "talking methods, " drawing on interviews conducted with academic researchers as part of the Methods for Change project. We highlight three creative talking techniques used within the project to elicit discussion of the transformative potential of social science methods: (i) how‐to instructions; (ii) object interviewing; and (iii) methods as animals. We argue that academics need to articulate why methods matter in creating change to global challenges, and that creative techniques can play a pivotal role.